2018
DOI: 10.4103/ijo.ijo_364_18
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional outcomes of pars plana vitrectomy for inflammatory epiretinal membrane surgery in healed toxoplasmosis infection

Abstract: Epiretinal membrane over macula secondary to toxoplasmosis compromises vision. We describe the outcome of pars plana vitrectomy and epiretinal membrane removal after adequate treatment of acute infection. The average age of all four male patients was 36 years (range 20–60 years). Following surgery there was an average three or more lines visual acuity improvement, restoration of foveal contour with reduction in central macular thickness. One patient developed choroidal neovascular membrane postsurgery and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…24 ERM is not an uncommon complication of ocular toxoplasmosis and results from the secretion of extracellular matrix and migration of glial cells, Müller cells, and fibroblasts in response to inflammation. 25 With improvements in OCT resolution, ERMs overlying active lesions and involving the macula are becoming more evident. 26 One patient in this case series developed a visually significant ERM ( Case 1 ) and had improved visual outcome after PPV with MP, similar to other reports.…”
Section: Discussionmentioning
confidence: 99%
“…24 ERM is not an uncommon complication of ocular toxoplasmosis and results from the secretion of extracellular matrix and migration of glial cells, Müller cells, and fibroblasts in response to inflammation. 25 With improvements in OCT resolution, ERMs overlying active lesions and involving the macula are becoming more evident. 26 One patient in this case series developed a visually significant ERM ( Case 1 ) and had improved visual outcome after PPV with MP, similar to other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases have reported that vitrectomy may be useful to address complications such as full-thickness macula holes, secondary epimacular membranes, and retinal detachment [ 9 - 12 ]. However, in this patient, as there was disorganization and fibrosis of the inner retinal layers at the papillomacular bundle found on OCT, vitrectomy may not result in adequate benefit for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Sousa et al (4) described a surgical case series including 11 patients submitted to PPV due to toxoplasmosis-related macular hole (TMH) and suggested this is a safe and effective therapeutic alternative. Raval et al (5) reported four cases of surgically treated epiretinal membrane. Postoperative anatomical and visual improvement in…”
Section: Discussionmentioning
confidence: 99%